A Bibliometric and Content Analysis of Articles in Remote Sensing From Vietnam Indexed in Scopus for the 2000–2019 Period. Issue 4 (1st October 2020) - Pham-Duc, Binh; Nguyen, Ho; Le Minh, Cuong; Khanh, Linh Hoang; Trung, Tran
Abstract: In this study, a bibliometric analysis is conducted to evaluate bibliographic content of all scientific publications in the field of remote sensing published by scholars with Vietnamese affiliations, indexed in the Scopus database, for the 2000–2019 period. Results indicated that the number of scientific publications in this research field increased gradually by years and then rapidly from 2015 with at least 50 articles per year. Most of the studies were concentrated in a few research institutions, and 65% of the publications were from top-10 Vietnamese research institutions. Vietnamese scholars had the most international collaboration with the USA, followed by Germany and Japan. The Mekong Delta is the most frequently studied area. Climate change, land-use change, groundwater, and landslides were the most popular research topics; machine learning and artificial neural networks were the most popular techniques studied in recent years.